Implementasi Data Mining dalam Pengolahan Data Transaksi Toko Sembako Menggunakan Algoritma Apriori (Studi Kasus : Toko Devan Mart) - Arin Nofianti; Mega Yuliani Yawan; Muarief Ahlun Nazar (Universitas Islam Raden Rahmat, Malang, 2023)
The business of selling groceries is now growing and there are more and more, so that the transactions that occur in each store are also increasing. But there are still lots of shops that don't know how to use the transaction data. Even though this data can be processed using data mining techniques which can later bring up new information that can be utilized, including this data can be used to determine the store's business strategy, determine the location of goods, and many other benefits. Given these problems, it is necessary to utilize the transaction data to be processed in data mining using an a priori algorithm so that it can provide new knowledge that can later be utilized by the shop. So based on research that has been done from processing 50 transactions from 10 days of sales at the Devan Mart store, it produces 5 rules that meet a minimum support of 12% and a minimum confidence of 50%.